Couvade syndrome: more than a toothache - Tess Chase; Adam Fusick; Jaimey M. Pauli (Taylor & Francis Group, 2021)
Background Couvade Syndrome is best characterized as a somatic symptom disorder where the partner experiences somatic symptoms during their partner's pregnancy most often during the first and third trimesters. Several psychoanalytical theories have been proposed for this disorder. There are well studied mood changes that correspond to hormonal shifts that occur in response to anticipated parenthood which serve as a physiologic mechanism for this pathology. Case The following is a case of Couvade syndrome in the setting of a high risk pregnancy complicated by pre-eclampsia with severe features necessitating a preterm delivery. Conclusion Expectant fathers should be screened for symptoms of Couvade Syndrome throughout the pregnancy in order to better support the familial unit.